Analysis of the Impact of Leadership, Organizational Culture, and Career Development on the Quality of Creative Industry Employees in Indonesia - Hendri Khuan; Robertus Adi Nugroho; Ni Desak Made Santi Diwyarthi; Nyoman Gede Mas Wiartha; Efa Irdhayanti (Westscience Press, 2024)
This research investigates the impact of leadership styles, organizational culture, and career development on the quality of creative industry employees in Indonesia. Using a quantitative approach, a sample of 300 professionals from the creative sector was analyzed. The measurement model evaluation confirmed the reliability and validity of the constructs, while the structural model revealed significant positive relationships between leadership styles, organizational culture, and career development with the quality of creative industry employees. The results provide valuable insights for organizational strategies and practices within the Indonesian creative industry, emphasizing the importance of visionary leadership, innovative culture, and career development opportunities in enhancing the quality of creative outputs.